Pengaruh Latihan Two Foot Sideways dan Icky Shuffle Terhadap Kelincahan Kaki Pada Atlet Tunggal Putra Bulu tangkis - Olivea Chinatta Otty; Shandy Pieter Pelamonia (Jurnal Ilmiah Adiraga, 2024)
This research focuses on how much influence two food sideways and icky shuffle have on the agility of the feet of badminton men's singles athletes. This type of research is a pseudo-experiment with a control group design research design. The data collection instrument uses a t test. The results showed the sig value for two foot sideways (X1) on foot agility (Y) was 0.003 <0.05. The sig value for icky shuffle (X2) on foot agility (Y) is 0.003 <0.05. These results indicate that there is a significant effect of two foot sideways and icky shuffle on foot agility. Keywords: Two Foot Sideways and Icky Shuffle, Agility.